Level of Satisfaction Using m-Banking: Tingkat Kepuasan Pemakaian m-Banking - Kholijah, gusmi; Br Ginting, Melva Silka (Jurnal Aplikasi Matematika dan Statistik, 2022)
Banks carry out activities to accommodate and distribute funds from the public to other communities, because the banking business relies on funds from the public that are stored in the bank concerned to be able to carry out its operations. Then, the more funds saved in the bank, the more developed the bank. The development of banks requires many people who become customers in a bank. Thus, to attract customers, banks issue products that aim to make it easier for people to make transactions, one of which is Mobile banking. Mobile-banking which functions as a service to facilitate online transaction activities. Therefore, to improve Mobile-banking services, it is necessary to evaluate the relationship between security, convenience, and speed of Mobile-banking services on bank customer satisfaction. To find out the relationship between security, convenience, and speed of Mobile-banking services on bank customer satisfaction, a contingency table with Chi-Square calculations can be used. The results showed that there is no relationship between customer satisfaction between the security and convenience of M-banking services. Customer satisfaction between security and speed of M-banking services is related. Customer satisfaction between the ease and speed of M-banking services has no relationship.